Sensitive determination of terazosin by x-ray fluorescence spectrometry based on the formation of ion-pair associates with zinc thiocyanate - Silva, Raúl Alejandro (2007)
A new, simple and precise indirect method for the determination of terazosin through x-ray fluorescence (XRF) is proposed. The method is based on the precipitation of an ion-associate complex formed between terazosin and [Zn(SCN)4]2- and the formation of a thin film on a membrane filter. The optimum conditions for ion-associate complex formation, such as pH, ionic strength, shaking time and stoichiometry of the complex, were studied. The complex was retained on the membrane filter, and the Zn Kα line was measured by XRF. The method presents the advantages of the separation of the drug from the matrix (excipients), the preconcentration of Zn, producing enhancement of XRF intensity though increased sensitivity, and the elimination of the matrix effects due to the thin film obtained. The lowest detection limit was 0.732 μg ml-1. The validation studies were realized by the related applications and the results were evaluated statistically. The method was successfully applied to terazosin determination in tablets or in bulk.